2017
DOI: 10.1007/s00709-017-1088-x
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 and H4 acetylation patterns are more dynamic than those of DNA methylation in Brachypodium distachyon embryos during seed maturation and germination

Abstract: The transition of seeds from a dry to a metabolically active state requires significant changes in both the spatial and temporal patterns of gene expression, and this transcriptional reprogramming involves various modifications of the chromatin structure. There are several factors that can greatly influence the structure of chromatin, one of which is the chemical modifications of histone proteins and DNA itself. In this study, we analysed the distribution of three epigenetic markers, i.e. acetylation of histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
(37 reference statements)
0
9
1
Order By: Relevance
“…Chromatin remodeling plays an important role in seed development, and it was previously proposed that chromatin dynamics could have a similar role in desiccation tolerance (35,52,53). We found no global changes in methylation during desiccation; however, we did observe an intriguing pattern of enrichment of H3K4me3 histone modifications upstream of genes down-regulated during desiccation.…”
Section: Discussioncontrasting
confidence: 44%
“…Chromatin remodeling plays an important role in seed development, and it was previously proposed that chromatin dynamics could have a similar role in desiccation tolerance (35,52,53). We found no global changes in methylation during desiccation; however, we did observe an intriguing pattern of enrichment of H3K4me3 histone modifications upstream of genes down-regulated during desiccation.…”
Section: Discussioncontrasting
confidence: 44%
“…Barrero et al [ 29 ] provided an anatomical description of Brachypodium caryopsis and also studied grain dormancy. Later, studies on the global histone modifications and DNA methylation changes during embryonic and postembryonic growth in Brachypodium [ 30 , 31 ] and on the breeding system, caryopsis structure, and germination [ 32 ] in annual and perennial Brachypodium species were performed.…”
Section: Discussionmentioning
confidence: 99%
“…The trimethylation of histone H3K4 plays a role in ABA-driven seed germination inhibition through the regulation of ABA-Hypersensitive Germination 3 ( AHG3 ) expression [ 138 ]. Wolny et al [ 139 ] indicated that histone H3 and H4 acetylation patterns were more dynamic than those of DNA methylation in Brachypodium distachyon embryos during seed maturation and germination. Analysis of seed dormancy cycling in Arabidopsis according to chromatin remodeling showed changes in trimethylated H3K4 (H3K4me3) and H3K27me3 on DOG1 in response to seasonal environmental signals [ 140 ].…”
Section: Mechanisms Of Adaptation Of Seed Germination To the Changmentioning
confidence: 99%